Stereotype-Based Managerial Identity Work in Multinational Corporations. Issue 9 (September 2016) - Koveshnikov, Alexei; Vaara, Eero; Ehrnrooth, Mats
The paper advances our understanding of managerial identity work in the context of HQ–subsidiary relations. We argue that a key part of this identity work is related to cultural stereotypes. On the basis of an analysis of two Finland-based MNCs operating in Russia, the paper elucidates three forms of stereotype-based identity work with enabling or constraining power implications. The first form, stereotypical talk, refers to identity work whereby managers enact their stereotypical conceptions of 'the other' to bolster their self-image and 'inferiorize' 'the other'. The second form, reactive talk, is identity work that emerges as a reaction to stereotypical talk whereby managers aim at renegotiating the proposed social arrangement for their own benefit. Finally, the third form, self-reflexive talk, refers to identity work whereby managers attempt to go beyond the social arrangement produced through stereotypical and reactive talk by distancing themselves in a self-reflexive manner from essentialist cultural conceptions. Overall, the paper offers an initial attempt to elucidate how stereotype-based identity work is used to justify or resist existing power structures and power asymmetries in HQ–subsidiary relations within the MNC.